2023
DOI: 10.1108/jsm-04-2022-0145
|View full text |Cite
|
Sign up to set email alerts
|

Exploring interactions between commuters with disabilities and transport service providers

Abstract: Purpose The purpose of this study is to explore the interactions between commuters with disabilities and transport services providers and to contribute to a better understanding of transformative service design, ensuring equitable access and the overall well-being of individuals. Design/methodology/approach This study collected qualitative data through ethnographic fieldwork and interviews with commuters with disabilities and transport services providers. The data were thematically analysed using NVivo. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 104 publications
0
3
0
Order By: Relevance
“…First, Sharma et al (2017) showed that co-creating value with customers with disability provides hedonic (pleasure and happiness) and eudaemonic (sense of achievement and purpose) well-being for these customers. Thus, malls could co-create solutions with shoppers with disability who are involved and willing to collaborate (a sometimes challenging goal due to the reluctance of service providers to cooperate; Mogaji and Nguyen, 2023). Second, malls could recruit and integrate more people with disability as employees in malls and consult them regularly.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…First, Sharma et al (2017) showed that co-creating value with customers with disability provides hedonic (pleasure and happiness) and eudaemonic (sense of achievement and purpose) well-being for these customers. Thus, malls could co-create solutions with shoppers with disability who are involved and willing to collaborate (a sometimes challenging goal due to the reluctance of service providers to cooperate; Mogaji and Nguyen, 2023). Second, malls could recruit and integrate more people with disability as employees in malls and consult them regularly.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…(2022) evaluate the role and experiences of women working in transport in the and French and Strachan (2009) evaluate opportunities for women in the Australian transport industry while not disparaging the lived experiences of women entrepreneurs in these developed countries; it is imperative to recognise that operating businesses in many of the African countries comes with its challenges. With inherent socioeconomic challenges around infrastructures, financial support, policies and regulatory requirement (Mogaji and Nguyen, 2021, 2023; Soetan et al ., 2021), prospective women transport entrepreneurs face various social, economic and cultural barriers which may not be present in developed countries.…”
Section: Extant Literaturementioning
confidence: 99%
“…Specifically, this article presents a unique perspective on the family business by exploring the internationality of experiences of women transport entrepreneurs in Africa. As illustrated in Figure 1, these women are sandwiched between the patriarchy and polygamous culture in many African countries (Cho et al ., 2018; Kiwia et al ., 2020; Oury Bailo et al ., 2023); second, the insufficient and inadequate infrastructures that affect business operations in Africa (Mogaji and Nguyen, 2021, 2023; Mousa and Arslan, 2023) and third, the societal expectations of women for women in a male-dominated, informal and unregulated transport services ecosystem (Akyelken, 2020; Luo and He, 2021). This commentary delves deeper into previous research on women in transportation, highlighting gaps in the literature and offering a practical perspective for the future.…”
Section: Introductionmentioning
confidence: 99%